THE COOPERATIVE LEARNING METHOD OF TEACHING IS AN IMPORTANT TOOL FOR IMPROVING STUDENTS’ COMMUNICATIVE COMPETENCE - Yuldasheva Dilfuza Kodirovna (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
The article informs about the teaching strategy and methods of training Cooperative learning, which use a variety of learning activities to improve students’ speaking skills. The author illustrates that this approach aims to enhance English communication abilities by strengthening grammatical understanding, language proficiency, and self-assurance to convey ideas clearly in everyday contexts. This method’s main goals help students become more proficient communicators in English.